If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(2x+67)=(103-9x)
We move all terms to the left:
(2x+67)-((103-9x))=0
We add all the numbers together, and all the variables
(2x+67)-((-9x+103))=0
We get rid of parentheses
2x-((-9x+103))+67=0
We calculate terms in parentheses: -((-9x+103)), so:We get rid of parentheses
(-9x+103)
We get rid of parentheses
-9x+103
Back to the equation:
-(-9x+103)
2x+9x-103+67=0
We add all the numbers together, and all the variables
11x-36=0
We move all terms containing x to the left, all other terms to the right
11x=36
x=36/11
x=3+3/11
| -10-4z=-8z+2z+10 | | 6x^2-12x-38=0 | | 1(-5y+-2)=23 | | 3w-93=2w-48 | | -9-c=9(-c-9) | | 4x-7/3x=14 | | 7w-95=2w | | -6.23-8.7y=-3.2y+7.46-6.54 | | -1-7k=7-3k | | 5(m-5)+2m=10m-34 | | 7w-95=7w | | 2w=7w-95 | | (-9w-5)=2(-5+5w) | | 3t-87=2t-52 | | 4(1+4v)=4v-32 | | 2t-52=3t-87 | | -10s+5=-8s-7 | | x^2-2x−4=-2x+5 | | 0.5n=6.25 | | -q+7=8-2q | | 5(x—3)=20 | | 25-8b=3(5-3b)+4 | | ((11.01*x)+(10.01*(1-x)))/100=10.81 | | -8-6m=-7m | | 8t+2=7+9t | | 3(1-3x)=2(-4+1x) | | -5-8z=7-5z | | 8+b/4b=20 | | 6-j/2=1 | | m/3+-3=-1 | | 3u=u+1 | | ((11.01*x)+(10.01*1-x))/100=10.81 |